PREREQUISITES FOR THE COACHING TECHNOLOGIES ORIGIN IN THE STAFF MANAGEMENT SYSTEM - О. Скоробагатська (Фізико-математична освіта)
Formulation of the problem. The new philosophy of staff management involves the formation of employees’ favorable work perception in the company, encouraging the interaction culture, the use of powerful analytics tools and giving employees the opportunity to control their own careers. Modern organizational coaching technologies help to build the potential of the staff management function, helping to achieve the goals of the organization.